2014
DOI: 10.1590/s1984-29612014049
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania infantum in Lutzomyia longipalpis captured in Campo Grande, MS

Abstract: Leishmaniasis is a zoonotic disease caused by protozoa of the genus Leishmania (Ross, 1903) and is the focus of considerable attention in human and veterinary medicine. In the city of Campo Grande, MS, the causative agent of visceral leishmaniasis is Leishmania infantum (= L. chagasi) primary vector, comprising approximately 92.9% of the local sandfly population, is Lutzomyia longipalpis. The aim of this work was to compare real-time PCR with PCR as a tool for the detection of the kinetoplast DNA (kDNA) of L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
1
10
0
3
Order By: Relevance
“…kDNA), which is present in high number of copies (~ 10,000 copies of minicircle molecules) per parasite [31]. In fact, other real-time PCR assays using the same target gene also reported very good analytical sensitivity [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…kDNA), which is present in high number of copies (~ 10,000 copies of minicircle molecules) per parasite [31]. In fact, other real-time PCR assays using the same target gene also reported very good analytical sensitivity [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the oral route as a transmission mechanism for Leishmania in bats cannot be ruled out because (i) phlebotomines including L. longipalpis are very abundant in CG (De Oliveira et al., ; Silva et al., ; Cunha et al., ), (ii) bats belonging to the family Phyllostomidae show a generalist diet, opportunistically consuming arthropods (Gardner, ; Bernard, ; Zortéa, ), (iii) A. lituratus , A. planirostris and C. perspicillata , which were found to be infected by Leishmania in the present study, have already been reported supplementing their diet with arthropods in the study area (Martins et al., ) and (iv) bats and L. longipalpis have overlapping crepuscular and nocturnal activity patterns (Rebêlo, ; Feliciangeli et al., ). Furthermore, it has previously been shown that bats can become infected by trypanosomatid species when they ingest parasitized insects (Thomas et al., ; Ramírez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the city of CG, thousands of L. infantum seropositive dogs are killed annually, but the increasing incidence of HVL and CVL shows that the existing control measures are not effective (Cunha et al., ). Therefore, the classic epidemiological approach involving dogs–shadflies–humans should be reconsidered in this urban environment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if a sample showed a high parasitic load, this may be due to one or more infected phlebotomines [64]. In Camaçari (Salvador) was performed a compared study in diferents periods of captures from L. longipalpis, the results of parasite load was low and did not vary regardless of the season, despite the number of collected sand ies [65].…”
Section: Discussionmentioning
confidence: 99%